Diagnosis of some genital-tract infections: part 2. Molecular tests and the new challenges. (March 2020) - Taylor-Robinson, David; Horner, Patrick; Pallecaros, Anna
Promptly and accurately diagnosing genital-tract infections is key to instituting appropriate treatment and control of sexually transmitted infections (STIs). Ano-genital tract testing for STIs in the last two decades has not entirely moved away from insensitive methods but it is now at least dominated by highly sensitive molecular methods. These tests can be ordered through the internet for use at home, with self-taken specimens then returned, usually by post, to a clinic or laboratory for testing. The increasing ease of access of the public to this situation, together with increasing on-line health-seeking behaviour, has resulted in a gap between commercial and NHS management pathways for STIs. Crucially, patients who order multiplex test kits on-line for use at home, and other non-specialists, may not realize that it is worthwhile testing only for Neisseria gonorrhoeae, Chlamydia trachomatis, and possibly Trichomonas vaginalis, and Mycoplasma genitalium if the person is symptomatic or their current partner is infected. The detection and recommended treatment of micro-organisms which to some extent are part of the genital-tract microbiome, such as Mycoplasma hominis, Ureaplasma spp. or Gardnerella vaginalis, which do not cause symptoms in the majority of those infected, cannot be recommended. We argue that a shift from specialist-led to patient- and non-specialist-led STI management, in the presence of a clinical leadership vacuum, has increased the risk of inappropriate and unnecessary treatment which will drive macrolide, tetracycline and metronidazole antimicrobial resistance. However, in the past 5–6 years several groups have been able to show the value of on-line testing as a consequence of targeting the most important micro-organisms and using molecular tests to allow rapid and appropriately informed treatment. This should herald a brighter future, although there is still a need for leadership to expertly guide commercial and NHS sectors alike. In turn, this requires dedicated genito-urinary medicine commissioning to be maintained at a time when it appears to be most under threat.